PREVALENCE OF ACUTE RENAL INJURY (ARI) AFTER CARDIAC SURGERY AT CONDUCTED AT TERTIARY CARE CARDIAC SETTING IN KARACHI.: http://doi.org/10.46536/jpumhs/2024/14.02.519 - Abida Iqbal1, Kashif Zia2, Iftekhar Shah3, Rabia Iqtdar4, Zubair Ahmed5, Mubashira Sadia6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUND: Cardiovascular disease (heart disease and stroke) is commonly recognized as the leading cause of mortality not just in the Western world, but also globally, accounting for a whopping 44% of total fatalities. Acute kidney Injury (AKI) is a common and significant prognostic complication of heart surgery. The total mortality rate following open-heart surgery is between 2 and 8%. OBJECTIVE: To determine the prevalence of Acute renal injury (ARI) after cardiac surgery at conducted at National Institute of Cardiovascular diseases, Karachi. MATERIALS AND METHODS: This descriptive cross sectional study was conducted at National Institute of Cardiovascular diseases, Karachi. Using a non-probability consecutive sampling technique 108 patients who underwent cardiac surgery were included in the study. RESULTS: The mean age was 62.5 ± 9.2 years, mean BMI was 28.2±7.5 and creatinine level was 1.89±0.54 mg/dl. Out of 108patients 5(4.63%) who underwent found to have post- surgery acute renal injury. CONCLUSION: The study revealed that acute renal failure following heart surgery is a prevalent outcome in our study population, but it is only mild to moderate in the majority of patients.